2016
DOI: 10.3390/md14090166
|View full text |Cite
|
Sign up to set email alerts
|

R-Phycoerythrin Induces SGC-7901 Apoptosis by Arresting Cell Cycle at S Phase

Abstract: R-Phycoerythrin (R-PE), one of the chemical constituents of red algae, could produce singlet oxygen upon excitation with the appropriate radiation and possibly be used in photodynamic therapy (PDT) for cancer. Documents reported that R-PE could inhibit cell proliferation in HepG2 and A549 cells, which was significative for cancer therapy. This is due to the fact that R-PE could kill cancer cells directly as well as by PDT. However, little is known about the cytotoxicity of R-PE to the SGC-7901 cell. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…When the cells begin to synthesize DNA during G1–S conversion, CDK2 will combine with its regulatory subunit cyclin E to form a Cdk2/Cyclin E complex, leading to Rb phosphorylation, and then E2F factor is released and cells are accelerated into the S phase [42]. During G0–G1 cycle arrest, the content of the CDK2/cyclin E complex decreases accordingly [43]. Our data showed that the protein expression levels of CDK2 and cyclin E in the SGC-7901 cells decreased after CBD treatment, which in turn reduced the formation of CDK2/cyclin E complexes, ultimately arresting SGC-7901 cells at the G0–G1 phase.…”
Section: Discussionmentioning
confidence: 99%
“…When the cells begin to synthesize DNA during G1–S conversion, CDK2 will combine with its regulatory subunit cyclin E to form a Cdk2/Cyclin E complex, leading to Rb phosphorylation, and then E2F factor is released and cells are accelerated into the S phase [42]. During G0–G1 cycle arrest, the content of the CDK2/cyclin E complex decreases accordingly [43]. Our data showed that the protein expression levels of CDK2 and cyclin E in the SGC-7901 cells decreased after CBD treatment, which in turn reduced the formation of CDK2/cyclin E complexes, ultimately arresting SGC-7901 cells at the G0–G1 phase.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of monitoring on cell cycle change is important for the development of drug delivery vectors, [37][38][39] and a few studies have reported that cell cycle arrest may lead to the induction of apoptosis. 40 Therefore, we investigated the effects of the cationic lipids on the cell cycle of NCI-H460 cells using flow cytometry after treatment with CDA14 and CDO14 for 24 h. At 15 μg mL −1 the two liposomes did not have any effects on the cell cycle phase.…”
Section: Effects On the Cell Cyclementioning
confidence: 99%
“…In the present study, CQ treatment induced a significant increase in the number of cells in the S phase and a decrease in the number of cells in the G 0 /G 1 phase in a concentration-dependent manner. S phase arrest accompanied with a decrease in the number of cells in G 0 /G 1 phase following treatment with antitumor drugs has also been reported in a number of other studies (31)(32)(33), and does not appear to affect the antitumor effect of these drugs. One potential explanation for this is that the inhibition of cell proliferation is associated with cell cycle arrest, but the phase at which the cells are arrested depends on the anticancer drugs and the antitumor cells involved.…”
Section: Discussionmentioning
confidence: 65%